Analysis methods of calculation for tolerance geodetic works in road construction to ensure set their altitude provisions - Yury Viktorovich Stolbov (Вестник СибАДИ, 2017)
The analysis methods for calculating allowances for geodetic works in prospecting and building roads to their predetermined height position. Examples of calculation of tolerances for surveying using equal and insignificant influence on the error of the final position of the structures and the method of taking into account the accuracy of technological processes in seeking and building roads. Calculated rate of accuracy of geodetic measurements in the detailed breakdown of marks surfaces of bases and covers, removal of marks pickets of workers frames and laying leveling moves along or on the highway Highway IV, V categories of public and agency using machines set without automatic system keeping predetermined elevations.